2021
DOI: 10.1002/stco.202000060
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the fatigue design of support structures for offshore wind turbines

Abstract: Extended keynote paper of Eurosteel 2021 This article provides an overview of the various support structures for offshore wind turbines and addresses the challenges that arise for the different design variants. First of all, the existing types of support structures are explained and their benefits and shortcomings discussed. Following that, the focus is on material fatigue and its analysis, which is of great importance due to the cyclic loading on the structures. A central topic of this article is the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As described in Section 3.1 some bending in the fastener has to be assumed due to the inclination of the fastener with regard to the force direction. Niebuhr and Sieder (2021) showed that the performance of the examined fastener is superior if the axial fastener stresses are caused by bending rather than an axial force as is known for other threaded fasteners such as steel bolts (cf., e.g., Agatonovic, 1973;Schaumann and Marten, 2009). Hence, a safe side approximation of the behaviour under bending or combined loading is possible with S-N-curves determined with pure axial loading if the actual fastener stresses with consideration of bending are utilised.…”
Section: Involved Fatigue Phenomenamentioning
confidence: 99%
“…As described in Section 3.1 some bending in the fastener has to be assumed due to the inclination of the fastener with regard to the force direction. Niebuhr and Sieder (2021) showed that the performance of the examined fastener is superior if the axial fastener stresses are caused by bending rather than an axial force as is known for other threaded fasteners such as steel bolts (cf., e.g., Agatonovic, 1973;Schaumann and Marten, 2009). Hence, a safe side approximation of the behaviour under bending or combined loading is possible with S-N-curves determined with pure axial loading if the actual fastener stresses with consideration of bending are utilised.…”
Section: Involved Fatigue Phenomenamentioning
confidence: 99%
“…As a synergy effect, an application of the digital image correlation (DIC) technique to cyclically loaded welded joints was developed to identify and analyse the transition from crack initiation to crack propagation [21]. By doing so, initial macroscopic cracks with lengths of about 1-1.5 mm could be detected [22], [23]. Owing to the chronological storage of the 3D digital images during the fatigue test, the DIC method used also includes the option of reviewing the history of the fatigue test and the 3D surface of the specimen to analyse, for example, the occurrence of outliers due to undercuts or sharp notches afterwards.…”
Section: Articlementioning
confidence: 99%
“…The tower has always played an important role in the total cost of a wind turbine, about 20 -30% of the total. Therefore, optimized and lightweight tower structures are important [1][2][3][4]. For wind energy branch, tubular steel towers are still the dominant tower concept.…”
Section: Introductionmentioning
confidence: 99%